Computer concepts : - Parsons, June Jamrich (Course Technology, 1998)
The third edition of this text offers greater integration between the text and state-of-the-art technology than the previous editions. Each text comes with a media-loaded CD-ROM that brings the text to life with numerous animations, graphics, videos, links to the Web and more.